2009
DOI: 10.1128/aem.01241-09
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Linker Length and Dockerin Position on Conversion of a Thermobifida fusca Endoglucanase to the Cellulosomal Mode

Abstract: We have been developing the cellulases of Thermobifida fusca as a model to explore the conversion from a free cellulase system to the cellulosomal mode. Three of the six T. fusca cellulases (endoglucanase Cel6A and exoglucanases Cel6B and Cel48A) have been converted in previous work by replacing their cellulosebinding modules (CBMs) with a dockerin, and the resultant recombinant "cellulosomized" enzymes were incorporated into chimeric scaffolding proteins that contained cohesin(s) together with a CBM. The acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 40 publications
7
94
0
1
Order By: Relevance
“…The results do not contradict the assumption that the assembly of the fully active cellulosomes is achieved by displaying a mature CipA protein on the outside of the cell; the independently secreted cellulosomal components seem to be assembled spontaneously by cohesindockerin interaction, as was shown previously with in vitro-created components (6,9,22).…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…The results do not contradict the assumption that the assembly of the fully active cellulosomes is achieved by displaying a mature CipA protein on the outside of the cell; the independently secreted cellulosomal components seem to be assembled spontaneously by cohesindockerin interaction, as was shown previously with in vitro-created components (6,9,22).…”
Section: Discussionsupporting
confidence: 45%
“…All of them used scaffoldin proteins with a limited number of cohesin-binding sites or a limited number of enzyme components (6,7,11,25,34,37). In most of these complexes, a specific dockerin-binding site was assigned to a certain enzyme component by using cohesin-dockerin pairs with different specificities.…”
Section: Discussionmentioning
confidence: 99%
“…Laccases, which facilitate the degradation of lignin, can largely contribute to current efforts to overcome limitations of enzymatic degradation of lignocellulosic biomass. In parallel, several studies have shown that highly efficient plant cell-wall degradation can be achieved by the use of the designer cellulosome complexes (20,21,37,52). Designer cellulosome technology, which harnesses the proximity effect of ordered hydrolytic enzymes to maximize their combined synergistic effects, was used in this work in combination with integration of a nonconventional enzyme that degrades lignin.…”
Section: Discussionmentioning
confidence: 99%
“…fusca enzymes involved in lignocellulose degradation have been extensively studied because they are industrially relevant due to their high thermostability, broad pH range, and high activity (19,37,42). In previous studies, the majority of these enzymes have been converted to the cellulosomal mode by fusion of a dockerin module, without adverse effects on their activity.…”
Section: Conversion Of the Selected Enzymes To The Cellulosomal Modementioning
confidence: 99%
See 1 more Smart Citation